Heritage Speakers as Part of the Native Language Continuum - Wiese, Heike; Alexiadou, Artemis; Allen, Shanley; Bunk, Oliver; Gagarina, Natalia; Iefremenko, Kateryna; Martynova, Maria; Pashkova, Tatiana; Rizou, Vicky; Schroeder, Christoph; Shadrova, Anna; Szucsich, Luka; et al. (Frontiers in Psychology, 2022)
We present results from a large-scale, cross-linguistic study that approached bilingual heritage speakers as native speakers of both their languages. We targeted comparable language use in bilingual and monolingual speakers, crucially covering broader repertoires than just formal language. A main database was the open-access RUEG corpus, which covers comparable informal vs. formal and spoken vs. written productions by adolescent and adult bilinguals with heritage-Greek, -Russian, and -Turkish in Germany and the U.S. and with heritage-German in the U.S., and matching data from monolinguals in Germany, the U.S., Greece, Russia, and Turkey. Our main results lie in three areas. (1) We found noncanonical patterns not only in bilingual, but also in monolingual speakers, including patterns that have so far been considered absent from native grammars, in domains of morphology, syntax, intonation, and pragmatics. (2) We found a degree of lexical and morphosyntactic inter-speaker variability in monolinguals that was sometimes higher than that of bilinguals, further challenging the model of the streamlined native speaker. (3) In majority language use, noncanonical patterns were dominant in spoken and/or informal registers, and this was true for monolinguals and bilinguals. In some cases, bilingual speakers were leading quantitatively. In heritage settings where the language was not part of formal schooling, we found tendencies of register levelling, presumably due to the fact that speakers had limited access to formal registers of the heritage language. Our findings point to an integration of heritage speakers into the native-speaker continuum that can shed light on language variation and change in native grammars. They indicate possible quantitative differences and different register distributions rather than distinct grammatical patterns in bilingual speakers and lead us to reconsider the state-of-the art on native grammars, given recurring evidence for noncanonical patterns that deviate from what has been assumed in the literature so far, and might have been attributed to bilingualism had we not included informal and spoken registers in monolinguals and bilinguals alike.